Proceedings of the 28th Conference on Winter Simulation - WSC '96 1996
DOI: 10.1145/256562.256882
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise modeling within an enterprise engineering framework

Abstract: The role of abstraction, or modeling, is a major element in Enterprise Engineering. Enterprise engineering deals with the analysis, design, implementation and operation of an enterprise. The Enterprise Engineer addresses a fimdarnental question: "how to design and improve all elements associated with the total enterprise through the use of engineering and analysis methods and tools to more effectively achieve its goals and objectives". This paper describes a describes a multi-view reference architecture for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 6 publications
0
20
0
5
Order By: Relevance
“…According to Aier and Saat [8], the involvement of heterogeneous stakeholder groups may create conflicting requirements in a complex environment. Hence, an appropriate communication and documentation of the enterprise models is vital, as stated by Liles and Presley [35]. For this purpose, and, as mentioned by Pulkkinen [40], because different stakeholders are interested in different levels of abstraction and granularities, different visualization types are needed (R9ab).…”
Section: R9) Specific Visualizations For Ea Planningmentioning
confidence: 99%
“…According to Aier and Saat [8], the involvement of heterogeneous stakeholder groups may create conflicting requirements in a complex environment. Hence, an appropriate communication and documentation of the enterprise models is vital, as stated by Liles and Presley [35]. For this purpose, and, as mentioned by Pulkkinen [40], because different stakeholders are interested in different levels of abstraction and granularities, different visualization types are needed (R9ab).…”
Section: R9) Specific Visualizations For Ea Planningmentioning
confidence: 99%
“…Although no previous examples were found documenting the industry-wide implementation of a distributed P2P traceability architecture, iii a review of literature pertaining to the successful development of complex systems identified the challenge of implementing a technology architecture analogous to the field of enterprise engineering. An enterprise refers to a complex system made up of interdependent pieces (people, information, and technology) that interact with their environment and each other in order to achieve a common goal (Liles and others 1995a,b;Liles and Presley 1996). Although the factors listed above have significant implications for the design and implementation of a global seafood traceability architecture compared to the situations into which other industry-wide interoperability has been enacted, iv many of the lessons learned and tools developed in enterprise engineering are applicable to the seafood industry, especially those pertaining to architectural design and testing.…”
Section: Virtual Testingmentioning
confidence: 99%
“…The goals of a particular study will necessarily impact the uses to which a model will be put and influence the requirements posed on the process techniques to be employed (Liles and Presley 1996). Table 1 illustrates typical process modeling goals and objectives, along with associated requirements for modeling techniques in each case (Curtis et al 1992).…”
Section: Bp/it Modeling Perspectivesmentioning
confidence: 99%